Book loss in academic law libraries characteristics and comparison of related factors - Dadang, Joan B.; Aguirre, Vyva Victoria M. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2007)
In spite of the safeguards and measures exercised by some selected law libraries in Manila to present possible losses of books, the problem of book loss still exists. This is clearly seen from the list of lost and/or missing books that these libraries incurred. This observation encouraged the researcher to undertake this study. Knowledge and awareness on the nature of the book losses in law libraries might help minimize, if not totally eradicate, this problem.
This study tried to find out the common characteristics of law books that put them at a higher possibility of being lost. The study also tried to compare the factors, namely: type of academic law library, existence of ESS, stack arrangement, and size of the collection in terms of the average number of book losses per year.
The study utilized a quantitative descriptive survey method, specifically cross-sectional design. This type of method was employed since the study focused in existing records of each law library for the past eleven years, from 1996 up to 2006. The population of the study included all academic law libraries located in Manila City. The sample was chosen based on the following inclusion criteria: (1) academic law library, (2) located in Manila, and (3) has an inventory list of lost and/or missing books during the period 1996 to 2006.Data obtained was analyzed using descriptive statistics: frequency distribution, percentile ranking and measures of central tendency, particularly the mean. The average number of book losses per year in each library was further analyzed to identify any significant differences in libraries in terms of stack arrangement, size of the collection, existence of an Electronic Security System, and the type of academic law library where the library was located. Independent samples t test (one-tailed right test) was utilized to test the differences.
Results showed that the characteristics of books lost in law libraries are: (1) Filipiniana material; (2) doctrinal writings, treatises, commentaries and textbooks which provides an in-depth discussion of the law and statute books which discuss the law itself; (3) books with subjects on civil law and other law-related books such as psychology, genetics, etc.; and (4) books with a publication year falling within the categories 1993-1999 and 1986-1992. The results also revealed that among the four independent variables, namely: type of library, existence of ESS, type of stack arrangement, and size of collection, only the existence of ESS and the type of stack arrangement variables are found to have significant differences in the average number of book losses per year.
It is highly recommended that law libraries implement an innovative procedure of monitoring lost/missing books in order to keep track of which books have a greater risk of getting lost.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Book thefts -- Philippines -- Manila; Law libraries -- Security measures -- Philippines -- Manila